An event of world-wide attraction - Matthias Schmitt (Intereconomics, 1968)
This year's Hanover Fair will be held from April 26 to May 5. As a display of technical achievement this fair has attracted world-wide attention and gained general recognition among the growing number of similar events. The number of German and foreign exhibitors, many of them with names known the world over, as well as the still rising flood of visitors are evidence of the Hanover Fair's prominent position, particularly in the sphere of investment goods. In order to learn how this event appears from the point of view of a large-scale enterprise we had a talk with Professor Dr Matthias Schmitt of the Allgemeine Elektricitaetsgesellschaft AEG-TELEFUNKEN about the significance of this year's fair and about some special aspects of fair policy.
Keywords: 330; Hanover-Fair 1968; Germany